2018
DOI: 10.1186/s12917-018-1373-8
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter volume in healthy and epileptic beagles using voxel-based morphometry – a pilot study

Abstract: BackgroundOne of the most common chronic neurological disorders in dogs is idiopathic epilepsy (IE) diagnosed as epilepsy without structural changes in the brain. In the current study the hypothesis should be proven that subtle grey matter changes occur in epileptic dogs. Therefore, magnetic resonance (MR) images of one dog breed (Beagles) were used to obtain an approximately uniform brain shape. Local differences in grey matter volume (GMV) were compared between 5 healthy Beagles and 10 Beagles with spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
(137 reference statements)
1
9
0
Order By: Relevance
“…However, given the time and effort required by trained clinical staff to extract the data, we do not advocate the use of this protocol for routine clinical application; rather we highlight the value of applying network analysis to complex clinical datasets. Whilst templates derived from a small number of breeds without structural brain pathology enable reproducible morphometric analysis 29,44,45,67 , these templates rapidly become inaccurate in the face of structural brain disease 44 . Milne et al ., attempted to account for craniofacial diversity in their development of brain atlas templates, however the patients used to generate these templates included neurologically abnormal dogs (with ataxia, vestibular disease, and idiopathic cerebellitis) and the assignment of craniofacial category was subjective 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, given the time and effort required by trained clinical staff to extract the data, we do not advocate the use of this protocol for routine clinical application; rather we highlight the value of applying network analysis to complex clinical datasets. Whilst templates derived from a small number of breeds without structural brain pathology enable reproducible morphometric analysis 29,44,45,67 , these templates rapidly become inaccurate in the face of structural brain disease 44 . Milne et al ., attempted to account for craniofacial diversity in their development of brain atlas templates, however the patients used to generate these templates included neurologically abnormal dogs (with ataxia, vestibular disease, and idiopathic cerebellitis) and the assignment of craniofacial category was subjective 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraneuronal inclusions identical to Lafora's bodies were detected in thalamic nuclei of only six dogs ( 152 ). Using MRI with voxel-based morphometry, we compared local differences in gray matter volume between 5 healthy Beagles and 10 Beagles with either idiopathic or structural epilepsy ( 267 ). Epileptic Beagles displayed statistically significant reduced gray matter volume in the olfactory bulb, cingulate gyrus, hippocampus, and cortex, especially in temporal and occipital lobes.…”
Section: Spontaneous Recurrent Seizures In Large Inbred Beagle Coloniesmentioning
confidence: 99%
“…This is particularly challenging given the conformational diversity of the dog [15], which is one of the most phenotypically diverse species on earth especially for the shape of the skull and cranial cavity [16]. In addition, automated voxel-based 2D morphometry techniques available in human medicine have only recently emerged in veterinary medicine [17,18], meaning that in most instances copious time and practice is essential to take such measurements [19]. Commonly used methods in veterinary medicine include: estimations based on area width, length and depth [20,21], volume rendering via slice-by-slice image segmentation [22] and manual pixel selection [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to human studies [12], many veterinary studies to date have focused on the volume or asymmetry of the lateral ventricles (LV) and have largely reported either no difference in total LV volume or left-right asymmetry in dogs with IE compared to controls [21,[23][24][25][26][27]. One veterinary study [28] found evidence of hippocampal atrophy in dogs with IE compared to controls whilst another found reduced grey matter volume in research beagles with and without spontaneous IE [17]. Most studies tentatively assume that these changes are incidental rather than evidence of pathology related to IE.…”
Section: Introductionmentioning
confidence: 99%